The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21272/jnep.12(5).05030
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Magnetoresistive Properties of Thin Film Alloys Based on Cobalt and Copper

Abstract: This work presents the results of a study of the influence of dimensional and concentration effects on magnetoresistive and magnetic properties and structural-phase state of annealed at Ta  700 K samples of thin film alloys based on Co and Cu with thickness d  40 nm in a wide range of total concentrations of Co (18 ≤ cCo ≤ 69 at. %). The samples were obtained by the method of co-evaporation in vacuum using two independent electron guns. It was found that samples of thin film alloys with a total concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another cause is surface anisotropy it could be suggested that the Co particles embedded in the Ag matrix are single-domain fine particles [39]. This perpendicular anisotropy has been observed in other granular films such as sputtered Ag-Co, Cu-Co, Co-Al-O and FeCoZr-CaF2 [14,18,19,[40][41][42][43]. In granulated materials the magnitude of the coercive force Hc depends on the size of magnetic granules [44,45].…”
Section: Tem Studymentioning
confidence: 93%
“…Another cause is surface anisotropy it could be suggested that the Co particles embedded in the Ag matrix are single-domain fine particles [39]. This perpendicular anisotropy has been observed in other granular films such as sputtered Ag-Co, Cu-Co, Co-Al-O and FeCoZr-CaF2 [14,18,19,[40][41][42][43]. In granulated materials the magnitude of the coercive force Hc depends on the size of magnetic granules [44,45].…”
Section: Tem Studymentioning
confidence: 93%